Climate change in Latin America and the Caribbean: Policy options and research priorities - Brian Feld; Sebastian Galiani (Latin American Economic Review, 2015)
Although climate change is filled with uncertainties, a broad set of policies proposed to address this issue can be grouped in two categories: mitigation and adaptation. Developed countries that are better prepared to cope with climate change have stressed the importance of mitigation, which ideally requires a global agreement that is still lacking. This paper uses a theoretical framework to argue that in the absence of a binding international agreement on mitigation, Latin America should focus mainly on adaptation to cope with the consequences of climate change. This is not a recommendation that such economies indulge in free-riding. Instead, it is based on cost-benefit considerations, all else being equal. Only in the presence of a global binding agreement can the region hope to exploit its comparative advantage in the conservation and management of forests, which are a large carbon sink. The decision of which policies to implement should depend on the results of a thorough cost-benefit analysis of competing projects, yet very little is known or has been carried out in this area to date. Research should be directed toward cost-benefit analysis of alternative climate change policies. Policymakers should compare other investments that are also pressing in the region, such as interventions to reduce water and air pollution, and determine which will render the greatest benefits.
Keywords: Q52; Q54; 330; Climate change; Adaptation; Cost–benefit analysis